Advocacy Journalism of Project Multatuli: A Discourse Analysis of Online Transportation Driver News Reporting - Zikrulloh, Zikrulloh (Universitas Multimedia Nusantara, 2024)
This study aims to discover how the online media Project Multatuli carries out advocacy journalism practices in voicing its support for marginal communities working as online motorcycle taxi drivers. This research was conducted using a qualitative approach. The unit of analysis used in this study is an article published on the online media project Multatuli in 2023 in the series rubric #SekrupKecil. Data analysis focused on text structure following the Critical Discourse Analysis framework developed by Teun A. Van Dijk. The study results show that the news broadcast in the #SekrupKecil series rubric meets the level of critical discourse analysis based on Teun A. van Dijk's model, which includes macro structure, superstructure, and microstructure. The study results also show that the practice of gamification and labor commodification is an issue often raised and given special attention by Project Multatuli as a practice of advocacy journalism.